Physical Fitness Of The Poomsae Taekwondo Athletes In Terms Of Agility, Balance And Endurance - Fahmy Fachrezzy; Uzizatun Maslikah; Endy Safadilla; Reggie Reginald; Singgih Hendarto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to determine physical fitness training to increase agility, balance, and endurance of taekwondo athletes State University of Jakarta Poomsae number. The sample used in this study of taekwondo athletes Poomsae number of 30 people.  The method used in this research is quasi-experimental design research using the design of one group pretest-posttest design. Data analysis techniques used in this study are using descriptive analysis and inferential analysis, descriptive analysis is used to describe the results of this research while inferential analysis using t-test with significant level = 0.05 analysis used with the help of SPSS version 20.0. The results of this study can be concluded that physical fitness exercises used have a significant effect on increasing agility, balance, and endurance in taekwondo athletes State University of Jakarta Poomsae number. In this study only involved physical fitness training to improve some physical components, but for further research, physical activity training methods and psychosocial and social environments will be carried out to improve the physical components of taekwondo athletes, especially in poomsae numbers to support qualified achievement.